2015
DOI: 10.1016/j.foodchem.2015.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the chemical components of taro rhizome mucilage and its emulsifying property

Abstract: The objective of this study was to determine the chemical composition of taro mucilage (TM) and explain its emulsification properties using different commercial emulsifiers and gums as benchmarks. The following analyses were performed: moisture, ether extract, protein, fiber, ash, sugar fraction, starch content, infrared spectroscopy and determination of monosaccharides and amino acids using HPLC. The analyses showed that TM has a high carbohydrate content and small protein fraction, similar to commercial gums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 19 publications
2
43
0
1
Order By: Relevance
“…The proposed mechanism of emulsifying activity of BSM is via the formation of multimolecular films around the droplets of the dispersed phase. Its excellent gelation behavior, ability to reduce the kinetic mobility and retard coalescence of the dispersed oil droplets have further improved the emulsion stability [9,10,36,37]. However, other formulations showed visible flocculation due to insufficient film formation and incomplete surface coverage of the oil droplets by the gum molecules as at higher concentrations, chains overlap or molecular crowding occurs which restricts diffusional transport of the molecules to and adsorption at the air-water interface [36].…”
Section: As Emulsion Stabilizermentioning
confidence: 99%
“…The proposed mechanism of emulsifying activity of BSM is via the formation of multimolecular films around the droplets of the dispersed phase. Its excellent gelation behavior, ability to reduce the kinetic mobility and retard coalescence of the dispersed oil droplets have further improved the emulsion stability [9,10,36,37]. However, other formulations showed visible flocculation due to insufficient film formation and incomplete surface coverage of the oil droplets by the gum molecules as at higher concentrations, chains overlap or molecular crowding occurs which restricts diffusional transport of the molecules to and adsorption at the air-water interface [36].…”
Section: As Emulsion Stabilizermentioning
confidence: 99%
“…According to Kizil et al, the band at 1642 cm −1 is associated to the water adsorbed in the amorphous region of starch and the variation in the intensity of this band can be related to the crystallinity. According to Andrade et al, this band is known as amide I band which is due to the CO stretching of the peptide groups revealing the presence of protein. In our study, this band could be associated with both: change of crystallinity due to the ball‐milling or presence of protein due to the use of all corm.…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectra of carbohydrates are commonly used for the determination of structural features [32]. As shown in Figure 4, the IR spectra of GUPS-I, GUPS-II, and GUPS-III had a broad, intense hydroxyl group stretching band at 3400-3300 cm −1 and a weak C-H stretching band at around 3000-2800 cm −1 , which are the characteristics of polysaccharides [12,33]. In the three spectra, the absorption peaks at approximately 1610-1655 cm −1 corresponded to carbonyl groups (C=O) and were caused by the bending mode of bound water, while the absorption peak at approximately 1400 cm −1 was the C-O stretching vibration [26,29,34,35].…”
Section: The Analysis Of Gups By Ft-ir Spectroscopymentioning
confidence: 99%
“…Many plant-derived polysaccharides have been extensively studied for immune enhancing effect because of their safety profiles [9]. Polysaccharides can activate macrophages, dendritic cells (DCs), T lymphocytes, B lymphocytes, and natural killer cells to produce immune-related molecules, such as cytokines, antibodies, and complement molecules [10][11][12]. Recently, several studies have shown that polysaccharides bind to receptors such as Toll-like receptors (TLRs) on the surface of macrophages or DCs to trigger several down-stream signaling pathways to promote immune responses [13,14].…”
Section: Introductionmentioning
confidence: 99%